2018
DOI: 10.2196/cardio.9000
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing User Experience Through User Study: Design of an mHealth Tool for Self-Management and Care Engagement of Cardiovascular Disease Patients

Abstract: BackgroundAs patient communication, engagement, personal health data tracking, and up-to-date information became more efficient through mobile health (mHealth), cardiovascular diseases (CVD) and other diseases that require behavioral improvements in daily life are now capable of being managed and prevented more effectively. However, to increase patient engagement through mHealth, it is important for the initial design to consider functionality and usability factors and accurately assess user demands during the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…Studies have found that the levels of user engagement greatly impact the outcomes of the interventions [31,32]. These findings support a user-centered design approach to developing digital health solutions [33]. In our study, we involved end users throughout the whole development process.…”
Section: Discussionsupporting
confidence: 52%
“…Studies have found that the levels of user engagement greatly impact the outcomes of the interventions [31,32]. These findings support a user-centered design approach to developing digital health solutions [33]. In our study, we involved end users throughout the whole development process.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, the ePRO app may indirectly activate engagement by improving communication with the providers using previously recorded data during routine consultations. The need to be more closely monitored by their physicians was reported by the patients during the FGs and has also emerged in previous app design studies [ 51 , 52 ]. Furthermore, the enhancement of communication links between the health care professionals and the patients, as well as the capture of patient-reported data, are considered among the 4 primary ways through which mHealth can improve the management of hemophilia A [ 14 ].…”
Section: Discussionmentioning
confidence: 95%
“…Despite these factors, it is disappointing that none of the secondary endpoints showed improvement, such as the Patient Activation Measure-13, which reflects patient knowledge, skills, and confidence in the management of chronic conditions 38 . The main purpose of the mHealth application was to enhance patients’ self-engagement 39 . Study participants in the intervention group accessed the application for a median of 11 days during the six-month study duration.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose, development, and details of the mHealth tool have been described previously 17 . The smartphone application, named HEART4U, works on both Android and iOS operating systems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation